By Phrases in Passives and Nominals. (31st May 2012) - Bruening, Benjamin
<x xml:space="preserve">Abstract</x> Abstract. A longstanding claim in the literature holds that by phrases are special in the passive, receiving certain external argument roles that by phrases in nominals cannot, such as the role of experiencer. This paper challenges this long‐standing claim and shows that by phrases are not special in the passive: they can receive all of the θ‐roles that they can in verbal passives. They are banned from certain nominals for the same reason they are banned from certain VP types like unaccusatives and sporadic advancements: by phrases require the syntactic and semantic presence of an external argument. By phrases can receive a uniform analysis, whether they occur with verbs or in nominals. The analysis proposed here involves syntactic word formation, with syntactic heads effecting passivization and nominalization. It also relies on syntactic selection for selectional features and proposes a theory of such features. The conception of grammar that emerges is one without lexical rules, where passivization and nominalization take place in the syntax.